2022
DOI: 10.7554/elife.73656
|View full text |Cite
|
Sign up to set email alerts
|

Notch-dependent and -independent transcription are modulated by tissue movements at gastrulation

Abstract: Cells sense and integrate external information from diverse sources that include mechanical cues. Shaping of tissues during development may thus require coordination between mechanical forces from morphogenesis and cell-cell signalling to confer appropriate changes in gene expression. By live-imaging Notch-induced transcription in real time we have discovered that morphogenetic movements during Drosophila gastrulation bring about an increase in activity-levels of a Notch responsive enhancer. Mutations that dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…Third, we found that NICD2 entered a nuclear microenvironment enriched in components associated with a transcriptional response as early as 30 to 45 min after GSI washout and that the molecular neighborhood associated with NICD2 persisted through the final 4-hour time point. This timing of transcriptional induction is consistent with previous real-time luciferase complementation studies using ectopic NOTCH1 and RBPJ expression ( 11 ) and with the onset and duration of Notch-induced transcription in fly models and in cancer cells ( 59 , 63 65 ). In addition to MAML1, the nuclear proteins most rapidly recruited to NICD2 were CREBBP/p300, a well-established partner of MAML1 in NICD-dependent transcriptional induction ( 57 , 58 , 66 , 67 ), and components of the BAF chromatin remodeling complex.…”
Section: Discussionsupporting
confidence: 90%
“…Third, we found that NICD2 entered a nuclear microenvironment enriched in components associated with a transcriptional response as early as 30 to 45 min after GSI washout and that the molecular neighborhood associated with NICD2 persisted through the final 4-hour time point. This timing of transcriptional induction is consistent with previous real-time luciferase complementation studies using ectopic NOTCH1 and RBPJ expression ( 11 ) and with the onset and duration of Notch-induced transcription in fly models and in cancer cells ( 59 , 63 65 ). In addition to MAML1, the nuclear proteins most rapidly recruited to NICD2 were CREBBP/p300, a well-established partner of MAML1 in NICD-dependent transcriptional induction ( 57 , 58 , 66 , 67 ), and components of the BAF chromatin remodeling complex.…”
Section: Discussionsupporting
confidence: 90%
“…No reuse allowed without permission. real-time luciferase complementation studies using ectopic Notch1 and RBPJ expression (Ilagan et al, 2011) and with the onset and duration of Notch-induced transcription in fly models and in cancer cells (Castel et al, 2013;Falo-Sanjuan & Bray, 2022;Housden et al, 2013;Wang et al, 2014). In addition to MAML1, the nuclear proteins most rapidly recruited to NICD2 are CREBBP/p300, a well-established partner of MAML1 in NICD-dependent transcriptional induction (Fryer et al, 2004;Fryer et al, 2002;Oswald et al, 2001;Wallberg et al, 2002), and components of the BAF chromatin remodeling complex.…”
Section: Discussionmentioning
confidence: 99%
“…NICD can access the nucleus within 30 min of ψ-secretase inhibitor removal (Martin et al, 2023) and can induce a transcriptional response in the nucleus within 60 min of Notch activation (Falo-Sanjuan & Bray, 2022; Ilagan et al, 2011). To quantify the amount of N2- C entering nuclei after cell-cell contact, we paired and imaged sender and receiver cells immediately (1-5 min) and 60 min after cell contact.…”
Section: Resultsmentioning
confidence: 99%